Réponses

2013-11-24T23:25:21+01:00
F = ((13/4)-(9/3))*((4/15)-(8/5))
F = ((39/12)-(36/12))*((4/15)-(24/15))
F = (3/12)*(-20/15)
F = (1/4)*(-4/3)
F = -4/12
F = -1/3

G = ((1/8)+(7/6))/((17/5-3/10))
G = ((6/48)+(56/48))/((34/10)-(3/10))
G = (62/48)/(31/10)
G = (31/24)/(31/10)
G = (31/24)*(10/31)
G = 310/744
G = 155/372
2013-11-24T23:28:52+01:00
F=(13x3/4x3-9x4/3x4) x (4/15-8x3/5x3)
= (39/12-36/12) x (4/15-24/15)
=(3/12) x ( -20/15)
=(3:3/12:3) x (-20/15)
=(1/4) x (-20/15)
=(1x15/4x15) x (-20x4/15x4)
= 15/60 x -80/60
= -1/3
G= (1/8+7/6) : ( 17/5-3/10)
=(1x3/8x3+7x4/6x4) : (17x2/5x2-3/10)
=(3/24+28/24) : (34/10-3/10)
=(31/24) : (31/10)
= 5/12